Deterministic Economic Resilience Through Gross Regional Domestic Product Using Nonparametric Geographically Weighted Regression Spline Truncated - Annisa, Nurul Mutiara; Octavia, Dhita Hartanti; Davala, Muhammad Ridzky (Universitas Bumigora, 2025)
Megatrends are large-scale global movements with huge impacts, influenced by socio-economic, political, ecological and technological factors. As a developing country, Indonesia faces challenges such as political instability and limited infrastructure, so strengthening economic resilience through increasing Gross Regional Domestic Product (GRDP) is important. The aim of this research is to analyze Indonesia's GRDP data in 2022, which shows significant spatial variability between provinces to see the resilience of the Indonesian economy. The method used is Nonparametric Geographically Weighted Regression - Spline Truncated (NGWR-ST). The NGWR-ST approach is well suited because it allows location-specific parameter variations, captures complex nonlinear relationships through spline functions, and minimizes the influence of extreme values ​​using truncation. The results indicate that an optimal model is achieved with two knot points (GCV = 0.293) and a fixed kernel bi-square weighting function with a 19.174 bandwidth (CV = 974.621), providing optimal spatial weighting. Among the factors analyzed, the Human Development Index (HDI) and the Rate of Return (ROR) are identified as having a significant influence on GRDP, contributing insights for strengthening Indonesia’s economic resilience. Thus, this study will contribute to formulating appropriate regional policy strategies to strengthen the economy in facing the World Megatrend in 2045